The role of bilateral ovariectomy in the impairments of prooxidant-antioxidant balance and renal concentrating capacity in rats in the period of late manifestations of the traumatic disease and the efficacy of hormone replacement therapy - I. Lutsiv; A. Hudyma; S. Halnykina; O. Denefil (Kazimierz Wielki University, 2021)
Introduction. Traumatic events are currently considered to be one of the topical issues. The progression of renal failure plays an important role in the pathogenesis of traumatic disease. It is essential to evaluate the ability of renal tubular epithelium to the urine osmotic concentration in order to indicate the direct renal tubular damage. A sodium-free water clearance (S-CH2O) is a sensitive indicator reflecting the kidneys ability to concentrate the urine. It is established that the renal functional state, the resistance of the kidneys to the development of various disorders depends on the estrogen concentration. The key mechanism of the indirect effect of estrogens on the kidneys is via their direct antioxidant action. However, the role of estrogens in the pathogenesis of oxidative and functional impairments of the kidneys in the presence of cranioskeletal trauma is insufficiently studied. There is no data available on the efficacy of hormone replacement therapy under those circumstances. The objective of research: to determine the pro-oxidant-antioxidant balance and renal concentrating capacity following the cranioskeletal trauma model in rats with bilateral ovariectomy in the period of late manifestations of the traumatic disease and evaluate the efficacy of hormone replacement therapy. Material and methods: The experimental studies were conducted on 64 white non-linear female rats weighing 200-220g. The experimental model of hypoestrogenism was performed through the surgical removal of gonads. The rats were subjected to the cranioskeletal model one month after removal of the gonads. Hormone replacement therapy (HRT) was used as a corrective treatment in the separate subgroup of gonadectomized rats subjected to the cranioskeletal trauma. The control groups consisted of intact animals and rats 1 month after removal of the gonads that were not injured. The renal functional state was determined via a water loading test in the control groups of animals and after 1 and 2 months of postrraumatic period. The sodium concentration, as well as the S-CH2O value was measured in serum and urine. The content of thiobarbituric acid reactive substances (TBARs) and catalase activity were determined in renal cortex and medulla. The prooxidant/antioxidant ratio (ProAntidex) was calculated based on the above data. The results and discussion. The conducted studies indicated the considerable decrease in ProAntidex value in renal cortex and medulla in the group of gonadectomized rats compared to the animals without gonadectomy after 1 month of the posttraumatic period, confirming the protective antioxidant role of estrogens in adequate renal function. The cranioskeletal trauma model led to the declined parameter value in renal cortex and medulla in both experimental groups after 1 month of the posttraumatic period. The prooxidant/antioxidant ratio was significantly decreased in the first month following the trauma in the gonadectomized rats as compared to the rats without the gonadectomy, and remained at the same level up to the 2nd month of the posttraumatic period. The identified abnormal value of ProAntidex in the posttraumatic period clearly affected the dynamics of S-CH2O. This parameter was reported as decreased in both experimental groups compared to the control. However, the parameter was substantially decreased 1 and 2 months after trauma under conditions of the gonadectomy.                   The administration of hexestrol and progesterone to the gonadectomized rats with trauma model resulted in the considerable increase in value of ProAntidex in renal cortex and medulla starting from the 1st day of the posttraumatic period compared to the animals without corrective medication. Moreover, it was accompanied by a statistically significant increase in S-CH2O rate, indicating the enhancement in the functional capacity of the renal tubules. Conclusions. The value of ProAntidex decreases in renal cortex and medulla in the group of gonadectomized female rats after 1 month of the posttraumatic period, and is significantly lower compared to the animals without removal of the gonads. The cranioskeletal trauma model leads to the substantially declined prooxidant/antioxidant ratio value in renal cortex and medulla, which is reported as considerably greater in the group of gonadectomized animals after 1 month of the posttraumatic period, showing no tendency to enhance after 2 months of the experiment. The administration of hormone replacement therapy to the gonadectomized rats is accompanied by the increase in ProAntidex value and S-CH2O rate compared to the animals without corrective medication.